2007
DOI: 10.1001/archotol.133.9.910
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Proteomic Approach for the Detection of Secretable Biomarkers of Invasiveness in Oral Squamous Cell Carcinoma

Abstract: To identify potential biomarkers of invasiveness in oral squamous cell carcinoma. Design: A pilot proteomic study for the identification of secreted and cleaved proteins that can serve as potential biomarkers for head and neck carcinoma invasiveness. Subjects: Two primary cell lines and their variants were established from 2 oral squamous cell carcinoma human tissue samples with distinct invasive phenotypes. The cell lines were confirmed to maintain the invasive capacity of the original cancer when implanted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We addressed the impact of Twist1 manipulation on the EMT phenotype using an NOE cell line, which was established from normal human tongue tissue, and the OSCC1.2 cell line, which was established from a poorly differentiated, metastatic, human oral cancer (stage T4N2b) that had vascular, lymphatic, and perineural invasion. 23,24 Exposure of NOE cells to TGFb induced a clear EMT phenotype in almost 100% of the population (Fig. 5A).…”
Section: Twist1 Is a Potential Therapeutic Target To Interfere With Omentioning
confidence: 94%
See 2 more Smart Citations
“…We addressed the impact of Twist1 manipulation on the EMT phenotype using an NOE cell line, which was established from normal human tongue tissue, and the OSCC1.2 cell line, which was established from a poorly differentiated, metastatic, human oral cancer (stage T4N2b) that had vascular, lymphatic, and perineural invasion. 23,24 Exposure of NOE cells to TGFb induced a clear EMT phenotype in almost 100% of the population (Fig. 5A).…”
Section: Twist1 Is a Potential Therapeutic Target To Interfere With Omentioning
confidence: 94%
“…22 The OSCC1.2 cell line was established by our group from a metastatic OSCC and was maintained in culture as previously described. 23,24 Small Interfering RNA Expression…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the established NET serum markers, chromogranins A, B, and C, were identified in the CM of all three lines, consistent with the neuroendocrine phenotype of these cells. These proteins have not been reported in the secretomes of several non-NET cell lines (11,13,(22)(23)(24) and were found in normal neuroendocrine secretory vesicles (21). However, these proteins possess limitations as NET biomarkers (see below).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based upon the assumption that the proteins secreted by the cell line will be representative of tumor cells in vivo. Studies have been performed using cell line models of prostate cancer, breast cancer (11), and head and neck cancer (13). Some putative markers were subsequently validated using immunological methods on limited numbers of clinical samples.…”
mentioning
confidence: 99%